Transitional approaches for PERN migration to SDN - Abdul Rahman, Abdul Malik; Rind, M. Malook; Koondhar, M.Y.; Shah, Asadullah (Science Alert, 2016)
With the emerging concepts of internet of things (IoT), bring your own device (BYOD), smart homes, vehicular adhoc networks 9VANETS), mobility and new service demands, legacy networking approaches are being considered complex and inefficient. In recent past a new approach called software defined networks (SDN) has emerged to revolutionize the four decades old networking approaches. The SDN's capacity to programmatically control and modify the network behavior has given extra edge to its wide scale proliferation. After some large scale successful deployments by Google, VMware, Facebook etc., SDN has attained huge research and vendor attention. Almost all large scale national research and education networks (NRENs) have prepared Opne flow based SDN test beds for collaborative future networking research.Pakistan education Research Network (PERN) project is still lagging behind in utilizing its network infrastructure for research and experimentation purpose. Although, green filed network migration of PERN is a challenging task and requires lot of budget and technical expertise, transitional approaches are the best way to migrate from legacy networking to SDN. This study highlights the role of SDN and its deployments in educational research networks for next generation network experimentation. This study proposes transitional approaches for the migration of PERN towards OpenFlow based SDN environment. In this study, it will also discuss how SDN based PERN can facilitate IT, telecommunications, software engineering, computer scientist and network engineering researchers in conducting future network experimentation.